2007
DOI: 10.1254/jphs.fp0061255
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine Activated Bcl-2 Expression and Inhibited Lipopolysaccharide-Induced Apoptosis in Hippocampus-Derived Adult Neural Stem Cells

Abstract: Abstract. Desipramine (DP) is a tricyclic antidepressant used for treating depression and numerous other psychiatric disorders. Recent studies have shown that DP can promote neurogenesis and improve the survival rate of hippocampal neurons. However, whether DP induces neuroprotection or promotes the differentiation of neural stem cells (NSCs) needs to be elucidated. In this study, we cultured NSCs derived from the hippocampal tissues of adult rats as an in vitro model to evaluate the modulation effect of DP on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 47 publications
0
30
1
Order By: Relevance
“…These findings suggest that Bcl-xL may play a pivotal role in mediating the anti-apoptotic effects of glucocorticoid in Ca3/7 cells. Huang et al reported that an increase in mRNA expression of Bcl-2, inhibition of caspases and apoptosis were induced by a low concentration of DMI (19). It is possible that the Bcl-2 family may be a key target in DMI-induced cell viability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that Bcl-xL may play a pivotal role in mediating the anti-apoptotic effects of glucocorticoid in Ca3/7 cells. Huang et al reported that an increase in mRNA expression of Bcl-2, inhibition of caspases and apoptosis were induced by a low concentration of DMI (19). It is possible that the Bcl-2 family may be a key target in DMI-induced cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…DMI has been shown to induce apoptosis in several cancer cell lines (13)(14)(15)(16)(17)(18)(19). In our previous study, we also examined the effect of DMI on the growth of three murine skin cell lines (3PC, MT1/2 and Ca3/7) representing different stages of skin carcinogenesis.…”
Section: Dmi Induces Apoptosis Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the same authors suggested that the contribution of cell death may have been underestimated, since antidepressant treatments are now known to be anti-apoptotic (Lucassen et al 2004). Since then, 3 investigations have responded to this comment: a) The antidepressant Desipramine is associated with cultured hippocampal neural stem cell neuroprotection against lipopolysaccharide-induced apoptosis by inhibiting inflammatory processes in vitro (Huang et al 2007); b) Desipramine and Fluoxetine increase Fibroblast Growth Factor-2 activity, a growth factor involved in maturation, synaptic connectivity, neurogenesis and survival of catecholamine neurons in the cortex and hippocampus ; c) Our own data, showing that Sertraline, an antidepressant with selective serotonin reuptake inhibition properties, blocks early post-MI apoptosis in the limbic system (Wann et al 2009). The anti-apoptotic effect of antidepressants was also reported in 2 other recent studies in rats (Huang et al 2007;.…”
Section: Post Myocardial Infarction Depression and Apoptosismentioning
confidence: 99%
“…Since then, 3 investigations have responded to this comment: a) The antidepressant Desipramine is associated with cultured hippocampal neural stem cell neuroprotection against lipopolysaccharide-induced apoptosis by inhibiting inflammatory processes in vitro (Huang et al 2007); b) Desipramine and Fluoxetine increase Fibroblast Growth Factor-2 activity, a growth factor involved in maturation, synaptic connectivity, neurogenesis and survival of catecholamine neurons in the cortex and hippocampus ; c) Our own data, showing that Sertraline, an antidepressant with selective serotonin reuptake inhibition properties, blocks early post-MI apoptosis in the limbic system (Wann et al 2009). The anti-apoptotic effect of antidepressants was also reported in 2 other recent studies in rats (Huang et al 2007;. Although apoptosis is difficult to document in human clinical cases (because patients are usually treated with antidepressants), another set of evidence indicates that the lymphocytes (Ivanova et al 2007) or blood leukocytes (Szuster-Ciesielska et al 2008) of depressed patients manifest a higher proportion of apoptotic elements compared to healthy controls.…”
Section: Post Myocardial Infarction Depression and Apoptosismentioning
confidence: 99%